Pelaksanaan Pembelajaran Tahfidz Al-Qur`An Dalam Membentuk Karakter Islami Siswa - Alwi, Toto; Badaruddin, Kms; Febriyanti, Febriyanti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the Learning of Tahfidz Al-Qur`an in shaping the Islamic character of Students at SD IT Islahul Ummah Prabumulih City. Learning evaluation The research was conducted at SD IT Islahul Ummah, Prabumulih City, 2022 to 2023. The research subjects were Tahfidz Al-Qur`an tutors, Madrasa Heads, Administrative Staff, and students of SD IT Islahul Ummah, Prabumulih City. This type of research is qualitative research. Data collection was carried out through interviews, observation, and document studies. All data collected was then analyzed in two stages. The first stage was when the data collection process was in progress, and the second stage after all data was collected was then analyzed by means of descriptive analytic. From this research, it was obtained an explanation that: 1) The Al-Qur'an tahfidz Learning Curriculum has been applied in the form of a syllabus 2). In learning, the supervising teachers have made a written plan, letters that must be memorized, 3). Implementation of Al-Qur'an Tahfidz Learning is carried out outside of class hours. 4). The method of memorizing the Qur'an uses the muroja`ah and sima`i methods. 4). The supervising teacher has a great influence on students in learning Taffid Al-Qur`an. 6). Learning Evaluation is carried out for each student's memorization deposit to the supervising teacher.